2010
DOI: 10.1007/s11069-010-9503-z
|View full text |Cite
|
Sign up to set email alerts
|

Site response studies in Mumbai using (H/V) Nakamura technique

Abstract: The importance of characterizing the site effects in urban areas, especially Mumbai, the commercial capital of India, with a quarter of land below sea level, is well realized. Mumbai is built on a cluster of seven basaltic islands that were merged together through reclamation of land from the Arabian Sea. Due to rapid urbanization, the demarcation between reclaimed areas and original islands is blurred. A pilot study is undertaken to investigate and characterize the local site effects at 27 locations in Mumbai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Mumbai city being financial capital of India, it is essential to study the seismic hazards and its effects on development of Mumbai city. Surve and Mohan (2010) had recently developed the H/V curves for identification of reclaimed land of Mumbai city and suggested that these curves will be useful inputs for seismic microzonation of Mumbai. Worldwide and within India, many attempts have been made to correlate values of shear wave velocity (V s ) with available soil parameters such as SPT 'N' value.…”
mentioning
confidence: 99%
“…Mumbai city being financial capital of India, it is essential to study the seismic hazards and its effects on development of Mumbai city. Surve and Mohan (2010) had recently developed the H/V curves for identification of reclaimed land of Mumbai city and suggested that these curves will be useful inputs for seismic microzonation of Mumbai. Worldwide and within India, many attempts have been made to correlate values of shear wave velocity (V s ) with available soil parameters such as SPT 'N' value.…”
mentioning
confidence: 99%
“…Several experimental studies (e.g., Lermo and Chavez-Garcia 1994;Theodulidis and Bard 1995;Malagnini et al 1996;Konno and Ohmachi 1998;Zaslavsky et al 2003;Parolai et al 2004;Mohamed et al 2008;Surve and Mohan 2010) found that the H/V technique provides reliable estimation of the fundamental frequency of soft deposits. In order to conduct seismic microzonation of Muscat city in terms of resonance frequency of the soil column, 459 field experiments using single-station microtremor measurements (Nakamura technique) were carried out (Fig.…”
Section: Fundamental Resonance Frequency Based On Microtremors Measurmentioning
confidence: 99%
“…Ambient noise observations are feasible to the acquisition, analysis time and an appealing approach for evaluation of ground response in large areas; these make this method ideal for characterizing the dynamic behaviour of shallow subsurface (Singh et al ., 2019). In recent times, this method has been widely used to study site effects to provide critical inputs for seismic microzonation and learn local geology (Surve and Mohan, 2010; Panzera et al ., 2015, 2017b; Kumar and Kumar, 2018; Macau et al ., 2018; Vicêncio et al ., 2018; Singh et al ., 2019). The HVSR method has been used to identify the sediment thickness over the bedrock, glacier thickness and local site effects (Parolai et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%